2020
DOI: 10.1016/j.jalz.2019.08.196
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and volumetric changes with increasing functional impairment in familial frontotemporal lobar degeneration

Abstract: IntroductionThe Advancing Research and Treatment in Frontotemporal Lobar Degeneration and Longitudinal Evaluation of Familial Frontotemporal Dementia Subjects longitudinal studies were designed to describe the natural history of familial‐frontotemporal lobar degeneration due to autosomal dominant mutations.MethodsWe examined cognitive performance, behavioral ratings, and brain volumes from the first time point in 320 MAPT, GRN, and C9orf72 family members, including 102 non–mutation carriers, 103 asymptomatic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 27 publications
2
37
0
Order By: Relevance
“…Our results showed that in all MAPT carriers combined, poorer memory performance was correlated with lower hippocampal volumes. Although hippocampal atrophy has been reported in MAPT , 2,3,6,8,17,36,38 to our knowledge, previous studies have not directly correlated memory performance with hippocampal volume in MAPT mutation carriers. The hippocampus is well‐established for its importance in episodic memory 19,20 and our results support that this structure underlies the memory impairment in MAPT .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Our results showed that in all MAPT carriers combined, poorer memory performance was correlated with lower hippocampal volumes. Although hippocampal atrophy has been reported in MAPT , 2,3,6,8,17,36,38 to our knowledge, previous studies have not directly correlated memory performance with hippocampal volume in MAPT mutation carriers. The hippocampus is well‐established for its importance in episodic memory 19,20 and our results support that this structure underlies the memory impairment in MAPT .…”
Section: Discussionmentioning
confidence: 64%
“…Although mean group w‐maps did not identify regions of low matter in presymptomatic carriers, frequency w‐maps revealed that 20% of this group had low mesial temporal volume. While early studies suggested that gray matter abnormalities were undetectable in presymptomatic MAPT mutation carriers, 4,5 recent larger studies suggested that presymptomatic carriers have low hippocampal and amygdalar volumes 6,8,17,38 . Several potential explanations may account for these varied results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathogenic variants in each of these genes are associated with overlapping but unique clinical and neuroimaging manifestations. 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Many studies have used brain atrophy to describe the evolution of neurodegeneration in f-FTLD, yielding the following observations: (1) cross-sectional atrophy can be detected in the presymptomatic stages, and each genetic group has different regional predilection for atrophy 3 , 6 , 8 , 12 , 13 , 14 ; (2) atrophy rates in the presymptomatic stages may exceed those of age-matched control cases 5 , 15 , 16 ; (3) the rate of volume loss may accelerate near the transition from asymptomatic to symptomatic 5 , 13 ; and (4) volume loss in symptomatic cases is usually well in excess of that in control cases. 16 , 17 , 18 However, conclusions from these observations are tempered because many analyses focused only on 1 genetic group or disease stage, limiting comparisons across genes and stages.…”
Section: Introductionmentioning
confidence: 99%